Transformasi Digital HR: Presensi dan Honorarium Dosen Melalui Sistem Informasi Akademik - Ulfa Sholihannlisa, Lulu; Ernawati (POLITEKNIK LP3I, 2025)
The problems that often arise from the use of manual attendance lists for lecturers result in discrepancies with the records of lecturer honoraria due to a lack of synchronization between attendance recording on the lecturer attendance list and the honor system. This study aims to provide an overview of the utilization of digital transformation of human resources regarding attendance and lecturer honor through SIAKAD. The research method is descriptive with a qualitative approach. Data analysis techniques were carried out using the Miles and Huberman model, which involves data collection, data reduction, data display, and conclusion drawing. The results that the understanding and experience of users demonstrate SIAKAD is very important for lecturers, assisting them in inputting attendance and maintaining the lecturer database. SIAKAD has also been effective where lecturers find it easy to use in the process, it can be accessed through the SIAKAD web, although there are some obstacles, they can be resolved by the academic department and the system's responsible party. In terms of efficiency and transparency, the honorarium is quite efficient and transparent, the impact on lecturers is that they are fairly productive because they have their own motivation fit and are satisfied with the existence of this SIAKAD